Research on the Unjust Enrichment Remedies for Personal Information Leakage in China - Xing, Weize (International Journal of Social Sciences and Public Administration, 2025)
As an important strategic resource, personal information data not only possesses personality interests, but also contains great economic potential. However, the problem of personal information leakage has become increasingly serious. Whether it is the traditional tort remedy or the“risk-based damage theory”, such problems are faced with practical or theoretical dilemmas, such as the difficulty of determining “damage” and the excessive burden of proof. Based on this, this article advocates the improper enrichment law as the core, to build a new type of personal information leakage relief path. First of all, unjustified enrichment relief path has the value of legitimacy and practical operability, through the personal information leakage is divided into “active leakage” and “passive leakage” of two kinds of situations, will be recognized as the rights and interests of infringement of unjustified enrichment, and based on the Chinese law, the law of unjustified enrichment is the most effective way to protect the rights and interests of the people of China. By classifying personal information leakage into “active leakage” and “passive leakage”, identifying it as unjustified enrichment, and based on Chinese law, interpreting the constituent elements and legal effects of unjustified enrichment on the basis of infringement of rights and interests, it not only can give full play to the complementary function of unjustified enrichment, but also can realize the relief of the subject of information.